2021
DOI: 10.1111/jocs.15575
|View full text |Cite
|
Sign up to set email alerts
|

Aortic dissection during pregnancy and postpartum

Abstract: Background: Patients with aortic dissection during pregnancy and postpartum period exhibit a high mortality. At present, a complete overview of aortic dissection during pregnancy and postpartum period is lacking.Methods: This systematic review included 80 reports published from 2000 to 2020, comprising a total study population of 103 patients with aortic dissection.Results: We found that Stanford Type A aortic dissection was more common in prepartum cases, especially in the third trimester, while postpartum ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 94 publications
(102 reference statements)
0
10
1
Order By: Relevance
“…The majority of pregnancy-related aortic dissection cases reported in previous studies were associated with connective tissue disorders (Marfan syndrome and Takayasu arteritis), hypertension, bicuspid aortic valve, and Turner syndrome. [12][13][14][15][16] However, no connective tissue disorder or other risk factors were identified in two of the patients in the present study, which suggested an unknown etiology of the disease.…”
Section: Discussioncontrasting
confidence: 59%
“…The majority of pregnancy-related aortic dissection cases reported in previous studies were associated with connective tissue disorders (Marfan syndrome and Takayasu arteritis), hypertension, bicuspid aortic valve, and Turner syndrome. [12][13][14][15][16] However, no connective tissue disorder or other risk factors were identified in two of the patients in the present study, which suggested an unknown etiology of the disease.…”
Section: Discussioncontrasting
confidence: 59%
“…It is an acute vascular pathology that is associated with various pathologies such as hypertension, atherosclerosis, hyperlipidaemia, and Marfan syndrome. The study of these related diseases not only aids to reveal the pathogenesis of renal cysts but also has positive implications for predicting the emergence of aortic coarctation [ 5 , 6 ]. In recent years, as research on aortic coarctation has intensified, some scholars have pointed out that renal cysts are more common in patients with aortic coarctation [ 7 ], but there are still few studies on the association between these two diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients have hypertension at the time of onset, and asymmetry of arterial blood pressure in bilateral extremities is also an important manifestation. [13] In this study, both patients had the above symptoms, and their symptoms were easily misdiagnosed as pulmonary embolism, coronary heart disease, and acute abdomen. When pregnant women have acute chest pain (70%), back pain (21.7%) or epigastric pain (2.5%), as well as dyspnea, persistent cough, syncope, and circulatory failure, the possibility of AD should be considered.…”
Section: Discussionmentioning
confidence: 83%